Strategi Komunikasi Tenant Relations dalam Menangani Keluhan Tenant di Gedung Gandaria 8 - Fauziah Rahmawati; Iin Soraya; Cindya Yunita Pratiwi (Dialogika : Jurnal Penelitian Komunikasi dan Sosialisasi, 2025)
Gandaria 8 Building is an office building that provides services for tenants with various business needs. One of the main focuses of Gandaria 8 Building management is to build good relationships with tenants and address their complaints through the Tenant Relations Division. This study aims to analyze the communication strategies implemented by the Tenant Relations Division in handling Tenant complaints at Gandaria 8 Building. The data collection methods used in this study include observation, interviews, and literature review, with a qualitative analysis approach. The Tenant Relations Division of Gandaria 8 Building implements communication strategies that involve the use of various communication media, such as telephone, email, and WhatsApp, along with a two-way communication approach that is friendly, open, and professional. The stages of handling Tenant complaints begin with complaint receipt, issue analysis, and resolution, ensuring prompt responses. The high level of empathy demonstrated by the Tenant Relations Division staff in responding to Tenant complaints is a critical factor in increasing Tenant satisfaction. However, challenges in documentation remain, necessitating improvements in the recording system to ensure complaints are well-documented and to facilitate monitoring of resolution status. By implementing effective communication strategies, the Tenant Relations Division of Gandaria 8 Building has successfully handled Tenant complaints, although there is still room for improvement, particularly in documentation management